Dual-wavelength laser generation using highly concentrated erbium-doped fibre coupling with microfibre knot resonator - Sulaiman, A.; Harun, Sulaiman Wadi; Ahmad, F.; Arof, Hamzah; Ahmad, Harith (2012)
A dual-wavelength fibre laser is demonstrated using a 2 m-long erbium-doped fibre (EDF) with a microfibre knot resonator (MKR) structure at the output end. The MKR is fabricated by heating and stretching an EDF to form a microfibre with diameter of around 2 mm, which is then manipulated to create a knot. At a loop diameter of 2 mm for the MKR, dual-wavelength laser is obtained at 1533.8 and 1555.4 nm with peak powers of 228.1 and 227.1 dBm, respectively. Both laser output is stable with a signal-to-noise ratio of more than 18.5 dB at room temperature.